2022
DOI: 10.2196/35677
|View full text |Cite
|
Sign up to set email alerts
|

Using Twitter to Examine Stigma Against People With Dementia During COVID-19: Infodemiology Study

Abstract: Background During the pandemic, there has been significant social media attention focused on the increased COVID-19 risks and impacts for people with dementia and their care partners. However, these messages can perpetuate misconceptions, false information, and stigma. Objective This study used Twitter data to understand stigma against people with dementia propagated during the COVID-19 pandemic. Methods We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Our findings parallel previous research on the prevalence of negative sentiments about aging (i.e., highlighting problems of old age and negative physical and functional implications of aging) on social media platforms ( Makita, Mas-Bleda, Stuart, & Thelwall, 2021 ). In particular, our findings are consistent with previous research highlighting social media posts containing ageist and stigmatizing content about older adults during COVID-19 ( Bacsu et al, 2022 ; Barrett, Michael, & Padavic, 2021 ; Jimenez-Sotomayor et al, 2020 ). Furthermore, the discourse on social media platforms during the COVID-19 pandemic contained posts perpetuating intergenerational divisions ( Soto-Perez-de-Celis, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings parallel previous research on the prevalence of negative sentiments about aging (i.e., highlighting problems of old age and negative physical and functional implications of aging) on social media platforms ( Makita, Mas-Bleda, Stuart, & Thelwall, 2021 ). In particular, our findings are consistent with previous research highlighting social media posts containing ageist and stigmatizing content about older adults during COVID-19 ( Bacsu et al, 2022 ; Barrett, Michael, & Padavic, 2021 ; Jimenez-Sotomayor et al, 2020 ). Furthermore, the discourse on social media platforms during the COVID-19 pandemic contained posts perpetuating intergenerational divisions ( Soto-Perez-de-Celis, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Other researchers have investigated public perceptions about people living with dementia based on Twitter posts (e.g., Cheng, Liu, & Woo, 2018 ; Robillard, Johnson, Hennessey, Beattie, & Illes, 2013 ). Bacsu et al (2022) , for example, identified Twitter post themes relating to misinformation, the perpetuation of ageist beliefs, as well as challenging the stigma against dementia during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Since significant social media attention focused on the increased COVID-19 risks and impacts for peo-ple with dementia, there were increased concerns that dementia-related stigma could have been spread on social media during the pandemic [42]. Our study is the first to quantify the level of dementia-related stigma before and during the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…Each tweet was coded independently by 2 coders to support intercoder reliability. All of our coders were experienced in conducting thematic analysis and have had previous experience in coding tweets [ 20 ]. Any coding uncertainties or disputes were resolved through discussion and consensus with 2 coders.…”
Section: Methodsmentioning
confidence: 99%